FAKTOR RISIKO DARI ASPEK MATERNAL PADA KEJADIAN BERAT BADAN LAHIR RENDAH (BBLR) DI WILAYAH KERJA DINAS KESEHATAN KOTA CIREBON TAHUN 2014 - Sheila Mahardini; Sri Achadi Nugraheni; Ronny Aruben (Jurnal Kesehatan Masyarakat (Undip), 2017)
Low birth weight (LBW) is one of the major nutrition problems that have an impact on neonatal mortality. In 2014 there were increase cases of low birth weight in the working area of the Cirebon City Health Office with the discovered of 195 cases (3.57%) and 7 of them died as a result of low birth weight. This issue was affected by many factors, and maternal risk factor was one of the major factors. The purpose of this study was to analyze the relationship between some of the aspects of maternal risk factors with low birth weight. This study was an observational analytic research with a case control approach. The source of data was derived from the secondary data in Puskesmas, such as registered cohort and card examination of pregnant women  The population were all babies born alive from January to December 2014 who were recorded in the region of Cirebon City Health Office especially in Pulasaren, Kesunean, Sitopeng, Sunyaragi, and Cangkol  Health Centers. Samples for each group were selected by purposive sampling method with the total sample was 70. Based on the results of chi square test with a significance level of 95%, the maternal risk factors that associated with low birth weight (p<0,05) were the size of the upper arm circumference (MUAC)(OR=8,206), fundal height (6,303), and blood pressure (OR=10,074),. The advices are monitoring nutritional status of mothers before and during pregnancy  more intensively, providing motivation and counseling to pregnant women to undergo regular prenatal care, optimizing the supplementary feeding program for pregnant women who have less nutritional status.